De-escalating treatment in the adjuvant setting in HER2-positive breast cancer. (28th March 2018) - Barroso-Sousa, Romualdo; Exman, Pedro; Tolaney, Sara M
The decision to offer adjuvant therapy to patients with early-stage cancer relies on factors related to the risk of disease recurrence, degree of benefit with the proposed therapy and the associated risk of toxicities. For patients with stages II and III HER2-positive breast cancer, administering 1 year of trastuzumab plus comprehensive chemotherapy is the standard of care. However, the pivotal adjuvant trials had very few older patients and patients with small HER2-positive tumors. In this review, we will discuss the clinical data regarding strategies to de-escalate adjuvant systemic therapy in patients with early stage HER2-positive disease.